ChemInform Abstract: Iron‐Catalyzed Borylation of Alkyl Electrophiles. Issue 6 (23rd January 2015) - Atack, Thomas C.; Lecker, Rachel M.; Cook, Silas P.
Abstract Optimized conditions concerning the amount of reactant, reagent and catalyst system are applied successfully to a broad spectrum of primary, secondary and tertiary bromides.